Interesting viewpoints on Laestadianism in Finland - Kejonen, Eetu (Approaching Religion, 2020)
Review of "Politiikka, talous ja työ. Lestadiolaisuus maailmassa", eds. Aini Linjakumpu, Tapio Nykänen, Tiina Harjumaa and Sandra Wallenius-Korkalo (Rovaniemi, Lapland University Press, 2019)